Prevalence of Maternal Measles, Rubella, Mumps and Varicella Antibodies in the First Six Months of Life - (:unkn) unknown (ANKARA MICROBIOLOGY SOC, 2018)
The protection of infants against infections during the first few months of life is provided mainly by maternal antibodies. The presence of maternal antibodies can decrease vaccine efficacy. The waning time of maternal antibodies shows variations therefore seroepidemiological studies are important for the development of vaccination schedules. Some recent studies showed that the maternal measles antibodies may disappear around 3 months of age especially in infants born from mothers who were vaccinated. There are few cross-sectional studies from Turkey evaluating the maternal antibody levels of infants against measles in recent years. The aim of this prospective, multicentre study is to evaluate the seropositivity of measles, rubella, mumps, and varicella in mothers and their infants at 1 and 6 months after birth. The study was carried out at the Social Pediatrics Units of two university hospitals, a private hospital and a state hospital. The exclusion criteria were known impaired immune system or immune deficiency disorder in mother or child, preterm delivery (< 37 gestational week), administration of immunoglobulins or any blood products before admission or during the follow-up period, and history of vaccination or exposure to one of these diseases during the study period. The final analysis encompassed 209 mother-infant pairs. Blood samples were collected 1 month after birth from mothers and 1 and 6 months after birth from their babies. Antibody levels were determined by ELISA (Enzyme-Linked ImmunoSorbent Assay) method. Information on the socio-economic and demographic characteristics of the families were collected by a face-to-face questionnaire. Seropositivity was found as 95.7%, 92.8%, 92.8% and 96.7% for measles, mumps, rubella and varicella (MMRV) respectively. Majority of infants lost maternal antibodies at 6 months of age. Of all 6 month-old infants 25% were seropositive for measles, 14.6% for mumps, 23.2% for rubella and 17.1% for varicella. The proportion of seropositive infants born from seropositive mothers was higher than those born from seronegative mothers for all four diseases. This difference was statistically significant only at 1 month of age (p=0.001). Our study showed that maternal antibodies against MMRV decreased rapidly by 6 months of age therefore necessary measures should be taken to close this gap between the loss of maternal protection and the vaccination of infants for MMRV. As the epidemiology of the diseases changes in time, it is important to carry out such studies with large series in different countries and settings. Important results were determined in our study within this respect.
Keywords: Maternal antibodies; measles; mumps; rubella; varicella; TURKEY